2021
DOI: 10.1080/00461520.2021.1898961
|View full text |Cite
|
Sign up to set email alerts
|

From old school to open science: The implications of new research norms for educational psychology and beyond

Abstract: Recently, scholars have noted how several "old-school" practices-a host of long-standing scientific norms-in combination, sometimes compromise the credibility of research. In response, other scholarly fields have developed several "open-science" norms and practices to address these credibility issues. Against this backdrop, this special issue explores the extent to which and how these norms should be adopted and adapted for educational psychology and education more broadly. Our introductory article contextuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…The research process has found some defects in pedagogy. These deficiencies are supplemented and improved through the study of EP ( Gehlbach and Robinson, 2021 ).…”
Section: Overview and Research Methods Of Educational Psychology Danc...mentioning
confidence: 99%
“…The research process has found some defects in pedagogy. These deficiencies are supplemented and improved through the study of EP ( Gehlbach and Robinson, 2021 ).…”
Section: Overview and Research Methods Of Educational Psychology Danc...mentioning
confidence: 99%
“…It is our arguement that people are more willing to accept amendments to their project at the design phase than at the completed phase, creating a more collegiate and discursive approach to peer review, which can only be to the benefit of science through the publication of more transparent methods and reliable findings. Furthermore, Gehlbach and Robinson (2021) points out that other transparent practices, such as pre-registering hypotheses and analyses, are not necessarily sufficient in ensuring better research practices and hence we believe that an outside review of the theory, methods, and analytical plan of a study before data collection can better show transparency and increase confidence in the conclusions.…”
Section: Improving Pedagogy Through Registered Reportsmentioning
confidence: 99%
“…That said, Gehlbach and Robinson (2021) postulated that within the field of educational psychology there is an uneven distribution of knowledge about the practices that lead to less credible research; it is not the case that all researchers are deliberately creating less reliable research, many are just not aware of the issue. And so, if replications, considered to be the gold standard in science and the approach that instils most confidence in research, are heavily under-used, potentially for reasons relating to the lack of novelty or, more simply, difficulty in replicating the study, and the current publication system ripe for the influx of questionable research, it would be pertinent to normalise an alternative approach to publishing research that counters these issues.…”
Section: Improving Pedagogy Through Registered Reportsmentioning
confidence: 99%
“…That is, other researchers can confirm the accuracy of reported findings by independently conducting the same analyses with the same data. Indeed, a recent Pew Research Center survey reported that among a sample of 3,627 U.S. adults, 57% said that they trust scientific research findings more when data are openly available (Funk, 2020).…”
Section: Benefitsmentioning
confidence: 99%